2016
DOI: 10.3390/s16010121
|View full text |Cite
|
Sign up to set email alerts
|

Realtime Gas Emission Monitoring at Hazardous Sites Using a Distributed Point-Source Sensing Infrastructure

Abstract: This paper describes a distributed point-source monitoring platform for gas level and leakage detection in hazardous environments. The platform, based on a wireless sensor network (WSN) architecture, is organised into sub-networks to be positioned in the plant’s critical areas; each sub-net includes a gateway unit wirelessly connected to the WSN nodes, hence providing an easily deployable, stand-alone infrastructure featuring a high degree of scalability and reconfigurability. Furthermore, the system provides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Case study-based results showed that the proposed system helped farmers make better decisions, improve citrus production, and reduce labor costs as well as the pollution caused by chemical fertilizers. Manes et al proposed a distributed monitoring system for leakage detection and gas levels in hazardous environments [ 9 ]. A wireless sensor network was utilized to gather the sensor data.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Case study-based results showed that the proposed system helped farmers make better decisions, improve citrus production, and reduce labor costs as well as the pollution caused by chemical fertilizers. Manes et al proposed a distributed monitoring system for leakage detection and gas levels in hazardous environments [ 9 ]. A wireless sensor network was utilized to gather the sensor data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent developments in information technology enable the integration of various monitoring applications into one complex system for the whole supply chain [ 6 ]. In general cases, the application of a monitoring system plays an important role in predicting disease [ 7 ], improving production, reducing cost [ 8 ], and providing an early warning system [ 9 , 10 ]. Recent technologies such as Internet of Things (IoT)-based sensors can be utilized and integrated with monitoring systems.…”
Section: Introductionmentioning
confidence: 99%
“…Given that pipeline installations transport gas from inaccessible and hard environments such as the desert and the bottom of the sea, providing local control and monitoring infrastructure is not economically feasible, and is in fact far from possible. Therefore, the use of the wireless sensor network and industrial internet of things is the best and economical solution for gathering data from the physical environment, and sending it to the control unit in order to decision‐making on the management layer …”
Section: Resultsmentioning
confidence: 99%
“…Significant research efforts have been carried out for achieving energy-efficient electronic devices capable of measuring the concentration of different pollutants in the air by monitoring applications and for evaluating the different approaches that were adopted [ 22 , 29 , 30 , 31 , 32 , 33 , 34 ]. We describe some of the most important works in this section.…”
Section: Related Workmentioning
confidence: 99%